Spatial Characteristics of Carbon Emission Networks in Selected Urbans within Pearl River Basin Area - YIN Jian; GAO Jielin; ZHANG Bin (Renmin Zhujiang)
Reducing urban carbon emissions is crucial for achieving global sustainable development. However, the complex interactions within urban spatial units make future urban carbon emissions uncertain, hindering the development of collaborative carbon emission reduction strategies in this area. To reveal the spatial complexity of urban carbon emissions, this study examines the changes in carbon emission collaborative relationships among relevant cities in the Pearl River Basin Areas in China, and formulate regional joint emission reduction plans according to local conditions. The study constructs a spatial connection network of urban carbon emissions based on the modified gravity model. The spatial complexity of carbon emission networks and the collaborative emission reduction potential are analyzed by complex network analysis and community division methods. The study reveals that the spatial complexity of the urban carbon emission network in the study area has increased, leading to an increase in the collaborative emission reduction effect among cities. Notably, Dongguan, Shenzhen, Guangzhou, Kunming, and Guiyang occupy a central position in the core network of carbon emissions and act as hubs for radiating influence. Additionally, the number of divisions within the urban carbon emissions network community declines, indicating a more concentrated set of common issues among urban carbon emissions and a heightened potential for cooperation. The proposed research framework can effectively analyze collaborative relationships in urban carbon emissions, providing a scientific basis for implementing differentiated collaborative emission reduction strategies.